Nancy Tatom Ammerman: Studying Lived Religion: Contexts and Practices - Petersen, Laura Bjørg Serup (Temenos, 2022)
Book review of Nancy Tatom Ammerman: Studying Lived Religion: Contexts and Practices. New York University Press, 2021, 257 pp.